Production and Characterization of Hydroxyapatite-Zirconia Composites - Ozmen, Melis; Akin, Ipek; Marsoglu, Muzeyyen (WALTER DE GRUYTER GMBH, 2012)
Hydroxyapatite (HA) ceramics are used extensively in different medical applications, such as biomaterial for repair or replacement of bone tissues since it resembles mineral component of bone and teeth. However, HA exhibits low fracture toughness due to its lack of strength and brittleness, thereby providing an obstacle to its application in implants that must withstand to high loads. In this study, HA was synthesized from human teeth by using a single calcinations method. Hydroxyapatite powders were mixed with different amounts of zirconia. The composites were sintered at different temperatures and characterized in terms of mechanical properties and the optimum sintering temperature was determined for good mechanical properties.
Keywords: Hydroxyapatite; zirconia; composite; sintering; CERAMICS; Materials Science